Analysis and Prospects of Developing Higher Education as a Key Factor of Economy Development (Comparative Analysis) - YERALINA, E. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The goal of this article is to define top priority areas of the education development for spreading innovative labor as a core factor of the economy development. Today, according to many indicators, the system of Kazakh higher education complies with standards of the developed countries. Every year the graduation of specialists of various levels increases. However, unlike the quality growth, the dynamics of quality indicators of the educational and professional preparation causes concerns, because its structure and content do not aim at forming the competences required for innovations. In this context, in accordance with the research methodology, the article defines criteria of developing the Kazakh education to spread innovative labor as a core factor of development. Based on them, it defines the results showing a considerable tendency towards social and humanitarian specialties in higher education while the labor innovation requires strengthening its technological component. As for technical education, the focus is made on the competences required for participating in engineering projects, which is not enough for scientific and research activity and developments. Against this background, it makes the conclusion about the need to modernize higher education whose leading vector is to train graduates for innovations.